Inhibition of Cyclic GMP‐AMP Synthase Using a Novel Antimalarial Drug Derivative in Trex1‐Deficient Mice. Issue 11 (14th September 2018) - An, Jie; Woodward, Joshua J.; Lai, Weinan; Minie, Mark; Sun, Xizhang; Tanaka, Lena; Snyder, Jessica M.; Sasaki, Tomikazu; Elkon, Keith B.
Abstract : Objective: Type I interferon (IFN) is strongly implicated in the pathogenesis of systemic lupus erythematosus (SLE) as well as rare monogenic interferonopathies such as Aicardi‐Goutières syndrome (AGS), a disease attributed to mutations in the DNA exonuclease TREX1 . The DNA‐activated type I IFN pathway cyclic GMP‐AMP (cGAMP) synthase (cGAS) is linked to subsets of AGS and lupus. This study was undertaken to identify inhibitors of the DNA–cGAS interaction, and to test the lead candidate drug, X6, in a mouse model of AGS. Methods: Trex1 −/− mice were treated orally from birth with either X6 or hydroxychloroquine (HCQ) for 8 weeks. Expression of IFN‐stimulated genes (ISGs) was quantified by quantitative polymerase chain reaction. Multiple reaction monitoring by ultra‐performance liquid chromatography coupled with tandem mass spectrometry was used to quantify the production of cGAMP and X6 drug concentrations in the serum and heart tissue of Trex1 −/− mice. Results: On the basis of the efficacy‐to‐toxicity ratio established in vitro, drug X6 was selected as the lead candidate for treatment of Trex1 −/− mice. X6 was significantly more effective than HCQ in attenuating ISG expression in mouse spleens ( P < 0.01 for Isg15 and Isg20 ) and hearts ( P < 0.05 for Isg15, Mx1, and Ifnb, and P  < 0.01 for Cxcl10 ), and in reducing the production of cGAMP in mouse heart tissue ( P < 0.05), thus demonstrating target engagement by the X6 compound. Of note, X6 was also more effective than HCQ in reducing ISG expression in vitro ( P < 0.05 for IFI27 and MX1, and P < 0.01 for IFI44L and PKR ) in human peripheral blood mononuclear cells from patients with SLE. Conclusion: This study demonstrates that X6 is superior to HCQ for the treatment of an experimental autoimmune myocarditis mediated in vivo by the cGAS/stimulator of IFN genes (cGAS/STING) pathway. The findings suggest that drug X6 could be developed as a novel treatment for AGS and/or lupus to inhibit activation of the cGAS/STING pathway.